Context specific adaptation grammars for climate adaptation in urban areas. (April 2018) - Radhakrishnan, Mohanasundar; Islam, Tushith; Ashley, Richard M.; Pathirana, Assela; Quan, Nguyen Hong; Gersonius, Berry; Zevenbergen, Chris
Abstract: In the context of climate adaptation planning there are relationships between adaptation drivers and adaptation measures, which makes the selection and implementation of the adaptation measures a challenging task. This challenge may be addressed by: structuring the adaptation problem using a multiple perspective adaptation framework; and applying a context specific precedence grammar logic for selecting and evaluating adaptation measures. Precedence grammar logic is a set of rule based algorithms (grammar) that are based on the relationships in a local adaptation context. This paper demonstrates the application of a context specific precedence grammar logic in an adaptation context in Can Tho, Vietnam. Adaptation pathways comprising flood adaptation measures (i.e. dike heightening) for this case were generated using rule based algorithms based on the relationships between the drivers and the adaptation measures. The results show that complex adaptation issues that are structured, can be resolved using a context specific adaptation grammar approach. Highlights: Urban adaptation is complex due to multiple adaptation drivers and responses. Adaptation can be structured using multiple perspectives. Interrelationships amid adaptation responses and drivers is contextual. Context specific adaptation grammar based on precedence grammar logic is proposed. City level and household response in complex adaptation context can be resolved.